Changes in the expression of small intestine extracellular matrix proteins in streptozotocin-induced diabetic rats - Sanchez, Sara Serafina del V. (2000)
Diabetes mellitus is characterized by anatomical and functional alterations of the intestinal tract. However, the aetiology of these disturbances remains unclear. The aim of the present work was to investigate the effects of diabetes on the expression of laminin-1 and fibronectin in the small intestine of Streptozotocin (STZ)-induced diabetic rats. The Western immunoblotting of the extracts from the small intestine revealed that experimental diabetes resulted in a marked increase in the intensity of the bands corresponding to laminin-1 and fibronectin. Immunohistochemical studies demonstrated a strong labelling to these two extracellular matrix (ECM) proteins in the small intestine of diabetic rats, mainly localized in the smooth muscle layer. These results occur together with a thickening of the basement membrane (BM) of the smooth muscle cells, demonstrated by transmission electron microscopy (TEM). We propose that the accumulation of ECM proteins in the smooth muscle layer may be an effect mediated by hyperglycaemia, since insulin treatment of diabetic rats reversed this accumulation. These results could provide information on the potential role of the ECM in the intestine, an organ which is known to exhibit important alterations in diabetes.